Effects of PCNL under the guidance of hologram technology on stress response and renal injury factors in patients with complex kidney stones: PCNL with Hologram Tech: Impact on Kidney Stone Patients - Liu, Changming; Dong, Zimin; Sheng, Mingxiong; Huang, Xinghua; Huang, Youfeng (Journal of Medical Biochemistry, 2024)
Background: To investigate the effect of percutaneous nephrolithotomy (PCNL) guided by holographic image technology on stress response and renal injury factors in patients with complex renal calculi.Methods: A retrospective analysis was conducted on the clinical data of 70 patients admitted to our hospital between August 2022 and June 2023 who had complex kidney stones. The patients were divided into two groups, namely, group A and group B, based on whether they received guidance from preoperative holographic imaging technology. Group A consisted of forty patients who underwent PCNL after undergoing renal CT examination prior to surgery, while Group B included thirty patients who underwent PCNL guided by holographic imaging technology. Various indexes, including operative factors, stress response, inflammatory response, renal injury factors, renal function, complication rate, and the rate of achieving complete stone clearance in a single procedure, were compared between the two groups.Results: In group B, the puncture time and operation time of the target calyces were shorter compared to group A, additionally, the intraoperative blood loss in group B was lower than that in group A (P